Evaluation of Muhadharah Program to Improve Students' Soft Skills - Ningsih, Salsabila Hady; Ahmadi, Ahmadi; Surawan, Surawan (LPPM Undiksha, 2025)
Students' non academic skills, especially soft skills, have not received much attention in the evaluation of Islamic values based programs. In fact, activities such as Muhadharah have the potential to support the development of these aspects. This study aims to thoroughly evaluate the effectiveness of the Muhadharah program in developing students' soft skills using the CIPP (Context, Input, Process, Product) evaluation model. A mixed methods approach was used, with data collection through questionnaires, interviews, observation, and documentation. Quantitative data were analyzed using percentage and Respondent Achievement Rate (TCR) techniques, while qualitative data were analyzed descriptively. The results showed that the Muhadharah program was in the “good” category in all four aspects of the evaluation. The program is relevant to students' needs, supported by adequate resources, implemented in a structured manner, and has a positive impact on improving speaking skills, self-confidence, cooperation, and other social skills. The study concluded that Muhadharah is an effective strategy in shaping soft skills through a religious approach. The implication of this study shows that the integration of religious activities and character strengthening is a relevant approach for modern Islamic education and can be replicated in other educational units with similar characteristics.